Cracking Failure Analysis of Pipe to Flange Weld Joint. Issue 1 (September 2021) - Yu, Lin; Liu, Yongliang; Deng, Hongda; Zhang, Shitong; Wang, Yang; Zhou, Yongzhi
Abstract: Cracking failures occurred frequently in blowdown pipe to flange weld joint, and the root crack appeared on the blowdown pipe side of the weld joint and extend into the base metal of pipe. To explore the reason why cracking failures occurred on the blowdown pipe side of the weld joint, the weld joint was analyzed via macroscopic and metallographic structure observation, and blowdown pipe was tested by physical and chemical property testing, and corrosion scale was analyzed by SEM, EDS, and XRD. The dent and thinner wall thickness of pipe are found in the internal pipe to flange weld joint. Widmanstatten metallographic structure is found in heat affected zone (HAZ), fusion zone (FZ) and weld metal zone (WZ) of weld joint. Stress concentration form in the weld joint at blowdown pipe side during welding due to the dent and different wall thickness. Under the action of gas vortex in the dent of weld joint, corrosive droplets aggravate the localized corrosion of the weld joint. Stress corrosion cracking (SCC) were initiated in FZ and WZ from the surface of weld joint and propagated into the base metal of pipe under the combined actions of stress resulting from weld process and during operation, and corrosion.